Avaliação de fontes de nitrogênio na produção de cana-de-açúcar, aporte de matéria orgânica no solo, e perdas por volatilização de amônia - SIQUEIRA, Elane Tyara de Jesus (2018)
The objective of this work was to evaluate the influence of different sources of N on the productivity and nutritive value of sugarcane, on the contribution of organic matter in the soil, and to quantify the losses of N by volatilization of ammonia, through different methodologies. The experiment was carried out at the Center for Agrarian and Environmental Sciences, Federal University of Maranhão, in the municipality of Chapadinha. Nitrogen sources (URE), chicken litter (CL), swine manure (SM) were used; and control (CON) where there was no fertilizer application, while the sugarcane variety used was RB92579. The dry matter (DM), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), lignin (LIG) were evaluated for the nutritive value of sugarcane. Brix, NDF / Brix ratio, and in situ degradability, in the incubation periods of 6, 24 and 72 hours; and also the yield of stalks. To evaluate N losses from nitrogen sources through ammonia volatilization, 3 different methods were used: open system (OP), semi-open chamber (SOC) and closed chamber (CC), with 7 sampling times (The total organic carbon (TOC), the particle size fraction of soil organic matter (COp and COam) and the total organic carbon content of the soil were evaluated. (OCC), at depths of 0-10, 10- 20 and 20-40 cm, in two soil samples at different periods, being these: before and after fertilization. It was possible to observe that the different nitrogen sources did not interfere in the sugarcane yield (P>0.05) of the sugarcane, with an average productivity of 102.1 t ha-1. The nutritional values of DM, CP, NDF, ADF, LIG, Brix and NDF / Brix ratio were also not affected (P>0.05) by nitrogen sources; on the other hand, the degradation of the DM showed an effect (P<0.05) for the sources and incubation times, where the treatments CL and SM presented higher degradation at 72 hours of incubation. For the NH3 volatilization results, the organic nitrogen sources SM and CL the largest losses occurred in the last collection times, with the SOC chamber being the most efficient. For the treatment with mineral nitrogen source URE the highest peaks of volatilization happened in the first collection times, in which the CSA once again presented greater efficiency when compared to CC and OP. Regarding the soil organic matter input, the organic fertilizer SM had a higher TOC content in the depth of 20-40 cm in the period after fertilization (P<0.05). For the granulometric fractions of the soil organic matter, there was no influence of the nitrogen sources in the COp for the depths evaluated in any of the collection periods, whereas for the COam contents the results presented similar patterns in the two collection periods, in which the SM, CL and CON treatments were superior in relation to URE in depth of 10-20 cm (P<0.05); and SM differed significantly from the other treatments at depth of 20-40 cm (P<0.05). The OCC, on the other hand, presented higher values for the SM treatment, which differed significantly from the other treatments at depths of 0-10 and 20-40 cm. It was possible to conclude that the organic sources can substitute the mineral fertilization of N, since they did not interfere in the chemical composition and productivity of the sugarcane crop, as well as they presented smaller losses N by volatilization of ammonia, with the SOC presenting greater efficiency; and improved soil quality.